2006
DOI: 10.1111/j.1530-0277.2006.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroadaptations of Cdk5 in Cholinergic Interneurons of the Nucleus Accumbens and Prefrontal Cortex of Inbred Alcohol‐preferring Rats Following Voluntary Alcohol Drinking

Abstract: This study identified Cdk5 neuroadaptation in cholinergic interneurons of the NuAcc and PFC and in other neurons of the CNA following 1 month of alcohol drinking. These findings contribute to our understanding of the cellular and molecular basis of alcohol drinking and toward the development of improved region and cell-specific pharmacotherapeutic and behavioral treatment programs for alcohol abuse and alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 122 publications
0
18
0
Order By: Relevance
“…In the brain, Cdk5 has been implicated in diverse biochemical processes involved in both functional and structural synaptic plasticity (21,52,53). Striatal Cdk5 levels are increased in response to chronic exposure to cocaine (15) and may be altered in response to voluntary alcohol drinking (54). Although the present study focuses on the role of Cdk5 in NAc, cocaine also induces increased expression of the kinase in dorsal striatum (15), which may also inf luence cocaine's behavioral effects.…”
Section: Discussionmentioning
confidence: 85%
“…In the brain, Cdk5 has been implicated in diverse biochemical processes involved in both functional and structural synaptic plasticity (21,52,53). Striatal Cdk5 levels are increased in response to chronic exposure to cocaine (15) and may be altered in response to voluntary alcohol drinking (54). Although the present study focuses on the role of Cdk5 in NAc, cocaine also induces increased expression of the kinase in dorsal striatum (15), which may also inf luence cocaine's behavioral effects.…”
Section: Discussionmentioning
confidence: 85%
“…In similar work, it has been shown that chronic ethanol drinking by P rats significantly up-regulated (~50%) cyclin-dependent kinase 5 (Cdk5, a marker of neuronal plasticity) immunoreactive cholinergic interneurons in the NAcc while significantly down-regulating (~50%) Cdk5 immunoreactive cholinergic interneurons in the infralimbic and prelimbic regions of the prefrontal cortex (Camp et al, 2006). Dopamine controls acetylcholine release and D1- and D2-like dopamine receptors have been identified on cholinergic interneurons of the NAcc (Alcantara et al., 2003, Berlanga et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…This reduction consists of lower numbers of Cdk5-immunoreactive cholinergic neurons in the PLC of those rats (Camp, et al, 2006). The lower numbers of PLC Cdk5-immunoreactive cholinergic neurons are concomitant with an increase in Cdk5-immunoreactive cells in the nucleus accumbens and amygdala.…”
Section: Discussionmentioning
confidence: 99%